2017
DOI: 10.1108/ijchm-11-2015-0641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of restaurant manager emotional intelligence and support on front-of-house employees’ job satisfaction

Abstract: Purpose This study aims to investigate the influence of restaurant manager’s emotional intelligence (EI) and manager support on service employees’ attitudes and performance by applying affective event theory. Design/methodology/approach The multi-level research approach incorporates three different levels of analysis: employees’ job satisfaction and service performance; manager’s EI and support; and) restaurant unit level service under pressure. Data were collected from wait staff employed in full-service re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 54 publications
2
19
0
9
Order By: Relevance
“…Thus, our results confirm our expectations that EI would be especially important to job performance for hospitality workers. Our research adds to a large body of prior research by corroborating the role of EI in boosting hospitality workers' job performance (e.g., Chen and Wang, 2019;Genc and Kozak, 2020;Han et al, 2017;Koc and Boz, 2020;Langhorn, 2004;Lee and Ok, 2012;Scott-Halsell et al, 2008).…”
Section: Theoretical Implicationssupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, our results confirm our expectations that EI would be especially important to job performance for hospitality workers. Our research adds to a large body of prior research by corroborating the role of EI in boosting hospitality workers' job performance (e.g., Chen and Wang, 2019;Genc and Kozak, 2020;Han et al, 2017;Koc and Boz, 2020;Langhorn, 2004;Lee and Ok, 2012;Scott-Halsell et al, 2008).…”
Section: Theoretical Implicationssupporting
confidence: 66%
“…Regarding the hospitality industry, Han et al (2017) found that restaurant managers with high EI increased employee satisfaction, which resulted in higher service performance. In a similar vein, Chen and Wang (2019) found that EI is positively related to job satisfaction and moderates the association between workplace incivility and job satisfaction for tourist hotel chefs.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The literature confirms that employees' job satisfaction influences turnover intention (Bufquin et al, 2017;Griffeth et al, 2000). Factors relating to employee job satisfaction include an employee's customer orientation and skill level, co-worker warmth and competence, manager emotional intelligence and support, as well as intrinsic motivation and supervisor leadership (Bufquin et al, 2017;Han et al, 2017;Kim and Jogaratnam, 2010). Stinchcombe (1965) suggests a company's social behavior reflects the pattern-setting influences that include values and beliefs as well as influence from the organization's founders.…”
Section: Ijchm 3110mentioning
confidence: 92%
“…Non-financial measures of success include employees' autonomy, JS and the ability to balance work and family responsibilities (e.g. Han et al, 2017;Shih et al, 2019).…”
Section: Financial/non-financial Performance: Linking Ewl With Performancementioning
confidence: 99%